Compliance with the Basel Core Principles and supervisory structure: A cross-country analysis - Maria Terese Medeiros Garcia; Frederico Cavaleiro de Mendonça (Central Bank Review (CBR), 2023)
This paper is motivated by the implementation of the new banking supervision structure in the European Union (EU) and the possible conflict of interest between monetary policy and the supervision authority within the European Central Bank (ECB). The empirical analysis considers the relationship between the structure of banking supervision and the compliance with the Basel Core Principles (BCP) for effective supervision. A sample of 21 countries and the Euro Area (EA) is used. In addition to the structure of bank supervision, a list of independent variables is considered to explain the dependent variable. The results suggest that the supervisory structure has no statistical significance at any notable significance level on compliance with the BCP. On the contrary, financial freedom is a statistically significant variable.
Keywords: C10; C50; E52; G21; G28; 330; Banking supervision; Basel core principles compliance; Central banking; Euro area; European central bank; Single supervisory mechanism